Misdiagnosis analysis of 2291 cases of haematolymphoid neoplasms - Deng, Jing; Zuo, Xiaona; Yang, Liuyi; Gao, Zifen; Zhou, Chunju; Guo, Ligai (Frontiers in Oncology, 2023)
Objective To retrospectively analyze the reasons for misdiagnosis of haematolymphoid neoplasms and provide experience for improving the diagnostic level in China. Methods A retrospective analysis was performed on 2291 cases of haematolymphoid diseases evaluated by the Department of Pathology of our hospital from 1 July 2019 to 30 June 2021. All 2291 cases were reviewed by two hematopathologist experts and classified according to the 2017 revised WHO classification criteria, supplemented immunohistochemistry (IHC), molecular biology and genetic information as needed. The diagnostic discordance between primary and expert review was evaluated. The possible causes of the diagnostic discrepancies were analyzed for each step involved in the procedure of diagnosis. Results In total, 912 cases did not conform to the expert diagnoses among all the 2291 cases, with a total misdiagnosis rate of 39.8%. Among them, misdiagnosis between benign and malignant lesions accounted for 24.3% (222/912), misdiagnosis between haematolymphoid neoplasms and non-haematolymphoid neoplasms accounted for 3.3% (30/912), misdiagnosis among lineages accounted for 9.3% (85/912), misclassification in lymphoma subtypes accounted for 60.8% (554/912), and other misdiagnoses among benign lesions accounted for 2.3% (21/912) of cases, among which misclassification of lymphoma subtypes was the most common. Conclusion The accurate diagnosis of haematolymphoid neoplasms is challenging, involving various types of misdiagnosis and complicated causes, however, it is important for precise treatment. Through this analysis, we aimed to highlight the importance of accurate diagnosis, avoid diagnostic pitfalls and to improve the diagnostic level in our country.